Environmental impact of human activities on water and sediment composition in Oginigba/Woji Creek, Port Harcourt, Nigeria - Ogan, Abiye Caleb (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
The environmental impact of human activities on water and sediment composition in Oginigba/Woji Creek, Port Harcourt, Nigeria, was investigated. The study has 7 objectives and 7 research questions. Four sampling stations were established along the study creek. The acid (HNO3) digestion method and the Aqua-Regia digestion procedure were used for the digestion of water and sediment samples, respectively. The determination of heavy metals was done with the Atomic Absorption Spectrophotometer (AAS). The mean spatial values of physicochemical parameters and heavy metal concentrations in surface water ranged as follows: Temperature (26.43±1.95–27.05±0.60℃), pH (6.6±0.65–6.8±0.47), Conductivity(10570.7±7543.3–15055.4±7505.7μS/cm), TDS(5813.92±4148.95–8280.6±4128.28mg/l), DO(5.56±0.79–5.75±0.86 mg/l), BOD5(1.95±0.07⎼2.28±0.07mg/l), Cd(ND), Pb(ND), Fe(0.19±0.17–0.28±0.17mg/l), Cu(0.09±0.01–0.18±0.01mg/l), Zn(0.20±0.02–0.35±0.02mg/l) and Mn(0.01±0.00–0.04±0.00mg/l). Spatial mean concentrations of water parameters were within safe limits, except for conductivity and TDS. Seasonal mean values were higher in the dry season, except for DO, Fe, and Mn concentrations, and varied significantly across seasons, except Zn and Mn. The spatial mean concentrations (mg/kg) of heavy metals in sediment ranged as follows: Cd(0.13±0.0–0.31±0.0), Pb (0.89±0.7–5.18±0.8), Fe(951.3±122.5–1809.2±437.8), Cu(4.35±0.46–11.45±1.99), Zn(13.07±2.16–34.93±6.58) and Mn(7.95±1.18–24.68±5.93); the spatial means of Pb, the spatial and seasonal means of Fe, and the dry season means of Cd and Pb exceeded the MPL. The spatial and seasonal means varied significantly, except for Fe about stations and Fe and Mn about seasons. The seasonal mean of heavy metals in sediment was higher in the dry season. The investigation revealed the sediment enrichment of heavy metals, most of them above safe limits. The elevated levels of the non-essential metals Cd and Pb in sediments constitute risk factors for benthic organisms, especially during the dry season, hence the need for restoration and corrective actions to mitigate the toxicity levels of these metals, not only for the wellbeing of aquatic species but also for the safety of human consumers of sea foods.